Influence of pyrolytic temperature on uranium adsorption capability by biochar derived from macauba coconut residue (Brazilian Journal of Radiation Sciences, 2019)
Biochar (BC) is a carbon-rich product obtained when biomass is thermally decomposed at relatively low temperatures (under 700ºC) and limited supply of oxygen in a process called pyrolysis. Because of its porous structure, charged surface and surface functional groups, BC exhibits a great potential as an adsorbent.  Its characteristics strongly depend on the feedstock and the pyrolysis conditions, in which the temperature is the key parameter. The aim of this study was to evaluate the adsorption potential for the removal of uranium, U(VI), from aqueous solutions using BC obtained through the pyrolysis of the macauba coconut endocarp as a function of the final pyrolytic temperature. The influence of parameters such as pH, sorbent dose and initial concentration on the adsorption of U(VI) was investigated. The maximum adsorption capacity (q) was achieved for the BC obtained at 250°C (BC250), which presented a removal percentage of approx. 86%, demonstrating the potential of the BC from macauba endocarp for treatment of wastewaters.